Analisis Penerapan Biaya Standar terhadap Pengendalian Biaya Produksi pada Javasublim - Anisa Gerhani Putri; Endah Dwi Kusumastuti (Indonesian Accounting Literacy Journal, 2022)
This study aims to determine how the application of standard costs to control production costs in Javasublim which produces jersey printing. The object of the research is the application of standard costs in increasing the efficiency of production costs. The research method used is descriptive qualitative method with interview and documentation data collection techniques and analysis techniques in the form of analysis of variance between production costs. The results show that Javasublim uses the production cost budget as a reference in the application of standard costs. Production cost control is done by analyzing production cost variance. The company has adequate standard costs, but in overhead standard there are still costs that are not charged consisting of costs for supporting raw materials, machine maintenance, and depreciation of fixed assets. The variance of unfavorable production costs is Rp 134.808.524. The average level of production cost efficiency is 69%, so the production cost is quite efficient. But the production cost has not been effective because it has an unfavorable variance.